2015
DOI: 10.1021/acschembio.5b00895
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Dynein Antagonists with Improved Potency and Isoform Selectivity

Abstract: Cytoplasmic dyneins 1 and 2 are related members of the AAA+ superfamily (ATPases associated with diverse cellular activities) that function as the predominant minus-end-directed microtubule motors in eukaryotic cells. Dynein 1 controls mitotic spindle assembly, organelle movement, axonal transport, and other cytosolic, microtubule-guided processes, whereas dynein 2 mediates retrograde trafficking within motile and primary cilia. Small-molecule inhibitors are important tools for investigating motor protein-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 40 publications
7
48
0
Order By: Relevance
“…4a ), similar to what has been observed previously [34, 35]. Anterograde and retrograde speeds were on the order of 0.7 μm/s, consistent with previously measured IFT velocities in mammalian cilia [3537]. To determine the impact of inhibition of KIF3A/KIF3B function on IFT, cilia expressing the inhibitable motor and IFT88-mNG were imaged and then B/B inhibitor, or ethanol vehicle as a control, was added and imaging of the same cilium was resumed.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…4a ), similar to what has been observed previously [34, 35]. Anterograde and retrograde speeds were on the order of 0.7 μm/s, consistent with previously measured IFT velocities in mammalian cilia [3537]. To determine the impact of inhibition of KIF3A/KIF3B function on IFT, cilia expressing the inhibitable motor and IFT88-mNG were imaged and then B/B inhibitor, or ethanol vehicle as a control, was added and imaging of the same cilium was resumed.…”
Section: Resultssupporting
confidence: 91%
“…Analysis of kymographs generated from live-cell imaging experiments revealed that IFT88-marked IFT trains moved processively towards the tip of the cilium, paused for variable durations, and then trafficked back towards the base ( Fig. 4a ), similar to what has been observed previously [34, 35]. Anterograde and retrograde speeds were on the order of 0.7 μm/s, consistent with previously measured IFT velocities in mammalian cilia [3537].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…To further improve the rigor and reproducibility/reliability of these findings, we also used a plasma membrane-permeable benzoyl dihydroquinazolinone derivative of AAAϩ ATPase motor cytoplasmic dynein inhibitor ciliobrevin D at the recommended dose range without cell cytotoxicity to inactivate dynein as earlier reported (14,72). Ciliobrevin D blocks ATPase activity in dynein 1 and disrupts spindle pole focusing and kinetochore-MT attachment (26,79). Ciliobrevin D is also known to reduce MT cycling Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The Hh signaling defects in dynein-2 mutants are similar to, but slightly milder than, loss of Kif3a or IFT-B mutants, suggesting that the loss of the retrograde motor disrupts cilia structure almost as completely as the loss of anterograde trafficking. Consistent with defects caused by mutations, chemical antagonists specific to cytoplasmic dyneins (the ciliobrevins) can inhibit dynein activity in vitro and in cells, and reduce both retrograde and trafficking and lead to the accumulation of IFT88 at the tips of cilia [68]. Mutations in human DYNC2H1 are implicated in two specific ciliopathies characterized by a constricted thoracic cage, short ribs, and shortened long bones: Jeune asphyxiating thoracic dystrophy (JATD) and short rib polydactyly syndrome (SRPS) (See table 1).…”
Section: Cytoplasmic Dynein-2: the Retrograde Ciliary Motormentioning
confidence: 99%